2017
DOI: 10.1080/07391102.2017.1396255
|View full text |Cite
|
Sign up to set email alerts
|

Ligand- and structure-basedin silicostudies to identify kinesin spindle protein (KSP) inhibitors as potential anticancer agents

Abstract: Kinesin spindle protein (KSP) belongs to the kinesin superfamily of microtubule-based motor proteins. KSP is responsible for the establishment of the bipolar mitotic spindle which mediates cell division. Inhibition of KSP expedites the blockade of the normal cell cycle during mitosis through the generation of monoastral MT arrays that finally cause apoptotic cell death. As KSP is highly expressed in proliferating/cancer cells, it has gained considerable attention as a potential drug target for cancer chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Alnylam Pharmaceuticals has successfully completed a Phase 1 clinical trial with ALN-VSP LNPs to treat advanced cancer with hepatic metastasis [ 104 ]. ALN-VSP comprises two siRNAs that target VEGF, which is critical for the growth of new blood vessels [ 105 ], and kinesin spindle protein (KSP), involved in cell division [ 106 ]. Upon parenteral administration, ALN-VSP passively accumulates in the liver, where it mediates anticancer activity.…”
Section: Delivery Issuesmentioning
confidence: 99%
“…Alnylam Pharmaceuticals has successfully completed a Phase 1 clinical trial with ALN-VSP LNPs to treat advanced cancer with hepatic metastasis [ 104 ]. ALN-VSP comprises two siRNAs that target VEGF, which is critical for the growth of new blood vessels [ 105 ], and kinesin spindle protein (KSP), involved in cell division [ 106 ]. Upon parenteral administration, ALN-VSP passively accumulates in the liver, where it mediates anticancer activity.…”
Section: Delivery Issuesmentioning
confidence: 99%
“…54 Several recent literature reports and patents in the field of pharmaceutical and medicinal chemistry demonstrated that this strategy is being adopted successfully in many drug discovery projects. 55 In light of the highly interesting literature reports with respect to the ongoing clinical evaluation of thiadiazole-based Eg5 inhibitors, and in continuation of our efforts to design and synthesize novel heterocyclic medicinal compounds, 25,[56][57][58] we herein report the synthesis, spectral characterization, and evaluation of novel thiadiazole-thiazolone (TDT) hybrid compounds as potential inhibitors of the MT-stimulated Eg5 ATPase. The molecular hybridization approach was employed for the design of novel Eg5 inhibitor core moiety (Fig.…”
Section: Clinically Available Antimitotic Agents Such As Vinca Alkalomentioning
confidence: 99%
“…YL001 inhibits the ATPase activity of the motor, blocks cells in mitosis and reduced melanoma tumor growth by 60% and significantly prolongs median survival time by more than 50% in a xenograft mouse model. A limitation of the virtual screening strategy is that although it may lead to the identification of small molecules that fulfill all the features of a pharmacophore, resembling those of known inhibitors, they may not display similar inhibitory activities in enzymatic and cell based assays [146]. To date, none of the identified Eg5 inhibitors by virtual screening have entered clinical trials yet.…”
Section: Virtual Screeningmentioning
confidence: 99%